Single-Cell RNA Sequencing Analysis Reveals Greater Epithelial Ridge Cells Degeneration During Postnatal Development of Cochlea in Rats - Chen, Jianyong; Gao, Dekun; Chen, Junmin; Hou, Shule; He, Baihui; Li, Yue; Li, Shuna; Zhang, Fan; Sun, Xiayu; Mammano, Fabio; Sun, Lianhua; Yang, Jun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Greater epithelial ridge cells, a transient neonatal cell group in the cochlear duct, which plays a crucial role in the functional maturation of hair cell, structural development of tectorial membrane, and refinement of audio localization before hearing. Greater epithelial ridge cells are methodologically homogeneous, while whether different cell subtypes are existence in this intriguing region and the degeneration mechanism during postnatal cochlear development are poorly understood. In the present study, single-cell RNA sequencing was performed on the cochlear duct of postnatal rats at day 1 (P1) and day 7 (P7) to identify subsets of greater epithelial ridge cell and progression. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis were used to examine genes enriched biological processes in these clusters. We identified a total of 26 clusters at P1 and P7 rats and found that the cell number of five cell clusters decreased significantly, while four clusters had similar gene expression patterns and biological properties. The genes of these four cell populations were mainly enriched in Ribosome and P13K-Akt signal pathway. Among them, Rps16, Rpsa, Col4a2, Col6a2, Ctsk, and Jun are particularly interesting as their expression might contribute to the greater epithelial ridge cells degeneration. In conclusion, our study provides an important reference resource of greater epithelial ridge cells landscape and mechanism insights for further understanding greater epithelial ridge cells degeneration during postnatal rat cochlear development.